Privatization of land and indigenous communities in Latin America: Tenure security or social security? - Søren Hvalkof (Danish Institute for International Studies (DIIS), 2008)
This working paper summarizes the discussions and findings of a recent study of the impacts of contemporary land privatization processes and individual titling programs affecting indigenous communities in Latin America, with particular emphasis on indigenous economies and production systems. The study was informed by case studies from Peru, Bolivia and Honduras and Mexico, with the main focus on the indigenous peasant societies of the highlands, where individualization schemes apply. The neoliberal policies of the 1990s promoted market based legal and administrative reforms, with a strong emphasis on developing a dynamic land market that would eventually have an impact on indigenous communal land tenure systems, whether they were the direct target or not. From the present study it can be seen that there are significant contradictions between indigenous communal land arrangements and tenure systems, and the market-based land and agricultural policy reforms being promoted by the multilateral donor agencies. In the conventional economic development discourse land tenure security is considered a prerequisite for economic growth. The study shows, however, that in relation to indigenous communities the question of tenure security is much more complex and closely related to the security of social reproduction, safeguarding of communal control and of the communal decision-making authority. It shows that privatization and individualization of land tenure per se has not generated the expected results.
Keywords: 330; Bodenreform; Agrarreform; Indigene Völker; Landwirtschaftliche Pacht; Bolivien; Honduras; Mexiko; Peru